Answering the call of duty: the phenomenology of justice in twenty-first-century video games. (2nd January 2015) - Newbery-Jones, Craig John
Abstract : In the twenty-first century, video games have become a major feature of the entertainment industry and a pervasive cultural medium. While cultural legal theory has examined other popular forms of culture, little attention has been paid to the relationship between law and justice in video games. Furthermore, the nature of law as a phenomenological experience is closely aligned with the experiential characteristics of video games. This differentiates video games from other modern cultural texts by providing the user with an active experience, instead of mere passive observation. This paper will interrogate these themes at their juncture, and explore how video games allow the individual to conceptualize and experiment with abstract themes, specifically justice. Furthermore, this article will argue that video games encourage the player to critically interrogate these themes in a more profound way than other modern texts due to their phenomenological characteristics.